Superior Supercapacitors based on Biowaste Materials - Bhat, V; S, Supriya; Hegde, G (University of Lampung, 2019)
Carbon nano spheres derived from Allium cepa were synthesized at differenttemperatures in a one-step pyrolysis process for supercapacitor electrodes. Obtainedcarbon nano spheres were analyzed using SEM, FTIR, BET and XRD. The nanomaterials were fabricated into conducting electrodes for cyclic voltammetry, constantcurrent charge-discharge and electrochemical impedance spectroscopy studies. All thestudies were done in 3.0 M KOH electrolyte. Specific capacitance from chargedischarge experiments were found to be 132.03 F/g and 149.49 F/g for nano materialssynthesized at 500ºC and 600ºC respectively. Obtained values suggest a way forward inproducing a green electrode for commercial applications.Keywords: Carbon nano spheres, supercapacitor electrodes, bio material